1993
DOI: 10.1073/pnas.90.13.6004
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila transforming growth factor beta superfamily proteins induce endochondral bone formation in mammals.

Abstract: Both decapentaplegic (dpp) protein and 60A protein have been implicated in pattern formation during Drosophila melanogaster embryogenesis. Within the C-terminal domain, dpp and 60A are similar to human bone morphogenetic protein 2 (75% identity) and human osteogenic protein 1 (70% identity), respectively. Both recombinant human bone morphogenetic protein 2 and recombinant human osteogenic protein 1 have been shown to induce bone formation in vivo and to restore large diaphyseal segmental defects in various ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 26 publications
(21 reference statements)
5
151
0
3
Order By: Relevance
“…BMP-2 is eluted only at high salt (0.7 M NaCI) and in the presence of 6 M urea from a heparin-Sepharose column . A direct physical binding of BMP-2 to heparin at physiological pH and salt concentrations, Celeste et al (1990) and Ozkaynak et al (1992), those of the Drosophila proteins from Sampath et al (1993). The bracketed residue in human BMP-2 is present only in the recombinant protein from E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-2 is eluted only at high salt (0.7 M NaCI) and in the presence of 6 M urea from a heparin-Sepharose column . A direct physical binding of BMP-2 to heparin at physiological pH and salt concentrations, Celeste et al (1990) and Ozkaynak et al (1992), those of the Drosophila proteins from Sampath et al (1993). The bracketed residue in human BMP-2 is present only in the recombinant protein from E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The mature BMP-2 protein is closely related to the Drosophila dpp protein (Padgett et al, 1993) and the Xenopus BMP-2 (Plessow et al, 1991). The human BMP-2 can substitute the Drosophila homologue dpp during dorsalventral patterning, and, vice versa, a recombinant dpp protein induces ectopic bone formation in rats (Padgett et al, 1993;Sampath et al, 1993). BMP-2 and the other BMP have great potential for medical therapeutic applications, in particular beCorrespondence to W. Sebald, Physiologische Chemie 11, TheodorBoveri-Institut fur Biowissenschaften (Biozentrum) der Universitat, Am Hubland, D-97074 Wiirzburg, Germany F a : f 4 9 931 888 4113.…”
mentioning
confidence: 99%
“…The remarkable conservation of these proteins and their mechanisms of action are illustrated by the ability of Drosophila dpp to initiate endochondral bone formation in mammals and the ability of the mammalian homologues of dpp (the BMPs) to replace dpp function in Drosophila (22,23). In addition, recent work based on phenotypic effects identified upon inactivation of members of this family also illustrates the crucial role for these proteins in tissue differentiation and interaction in organisms as diverse as Drosophila and humans (Ref.…”
mentioning
confidence: 99%
“…Previous studies have reported that the bone-forming activity of the Drosophila dpp protein can be demonstrated by measuring the specific activity of ALP and the calcium content in subcutaneous rat implants (Sampath et al , 1993). The B. mori dpp gene shares genetic homology with hBMPs and Drosophila dpp.…”
Section: Resultsmentioning
confidence: 99%
“…The hBMP-4 transgene can rescue dorsal embryonic pattern defects in Drosophila dppmutant flies (Künnapuu and Shimmi, 2010;Padgett et al , 1993). In contrast, Drosophila dpp induces bone formation in mammalian cells (Künnapuu and Shimmi, 2010;Sampath et al , 1993). Moreover, the ligands of BMP-2, BMP-4, and dpp have evolutionarily conserved roles in embryonic development (Künnapuu and Shimmi, 2010).…”
Section: Construction Of Mammalian Cell Expression Plasmidmentioning
confidence: 99%